Self Confidence Siswa dalam Menyelesaikan Tugas dan Implikasinya terhadap Layanan Bimbingan dan Konseling - Maretha, Anngi Adrian; Ibrahim, Indra; Said, Azrul (Universitas Negeri Padang, 2014)
It was assumed that students who had self-confidence would be able to complete their tasks and vise versa. In fact, there were still some students had less self-confidence in completing their tasks. This researchwas aimed at describing the students’ self-confidence at SMA Negeri 1 Lubuk Sikaping in completing their task. This was a descriptive research whose population was 592 students. From those, 86 students were taken as the sample. The data was collected by using questionnaire. The result of the research revealed that the students’ self-confidence at SMA Negeri 1 Lubuk Sikaping was in good category. To increase students’s self confidence in completing thein tasks better, the guidance and counseling teachers give them information service, team guidance service, and individual counseling.